Obstruent voicing effects on F0, but without voicing: Phonetic correlates of Swiss German lenis, fortis, and aspirated stops. (November 2018) - Ladd, D. Robert; Schmid, Stephan
Highlights: Swiss German fortis and lenis stops are distinguished by closure duration but not by VOT. F0 drop following both types of stop resembles voiceless F0 perturbations in other languages. Fortis/lenis F0 effects may also involve typical voicing-related differences of F0 level . Marginally contrastive aspirated stops show speaker variation in both VOT and F0 patterns. Abstract: It is well known that what are commonly called voicing contrasts in many languages are accompanied by effects on the fundamental frequency (F0) of a following vowel: roughly, F0 is higher after 'voiceless' and lower after 'voiced' obstruents. This is true regardless of how the voicing contrast is manifested in differences of voice onset time (VOT). Such effects potentially provide a window on the nature of voicing itself, but our knowledge is based primarily on typical European two-way voicing contrasts. Here we present a detailed study of voice onset time (VOT), closure duration, and obstruent F0 effects in Zurich Swiss German. The native two-way contrast in oral stops (often termed fortis/lenis) is unusual in being signalled not by VOT – both types are unaspirated – but primarily by closure duration. We confirm studies showing that this distinction is indeed based on duration, and we show for the first time that both types are accompanied by F0 effects that are typical of voiceless obstruents in other languages. In addition, Swiss German has a smallish set of words conventionally pronounced with voiceless aspirated stops. We investigate the VOT and F0 effects of these marginally contrastive aspirated stops, showing that they do exhibit long VOT and are accompanied by a different pattern of F0 effects that is much more variable than that found with fortis and lenis stops. Our findings support the view that the phonetic basis of voicing and related distinctions involves complex interactions of timing and articulatory gestures that cannot always be characterised in terms of a simple VOT continuum from 'voiced' to 'voiceless aspirated' or a simple phonological dichotomy between 'aspirating' and 'true voicing' languages.